If the expression + + ...... +
Can be written as - , Find a+b.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note first that
n! + (n+1)! + (n+2)! = n! * (1 + (n+1) + (n+1)(n+2)) = n! * (n+2)^2.
Thus (n+2) / (n! + (n+1)! + (n+2)!) = 1 / (n! * (n+2)) = (n+1) / (n+2)! =
[(n+2) / (n+2)!] - [1 / (n+2)!] = [1 / (n+1)!] - [1 / (n+2)!].
So now we end up with a telescoping series with n going from 1 to 1999. All the terms will cancel except for the first and last, leaving us with [1 / 2!] - [1 / 2001!], making a=2 and b=2001, and so a + b = 2003 is the final answer.